Community-Driven Approaches in Lao PDR : Moving Beyond Service Delivery - Summary Overview - World Bank (World Bank, Washington, DC, 2012)
This report reviews Community Driven Development (CDD) projects in Lao People's Democratic Republic (PDR) to determine their effectiveness in channeling resources to communities for poverty reduction. The study examines three CDD projects in depth: the Poverty Reduction Fund, the Village Investment for the Poor (both supported by the World Bank), and the Government-financed Village Development Fund. Through close analysis of these projects and cursory analysis of other CDD projects, the report concludes that overall, the CDD approach in Lao PDR improves the well-being of communities in a cost-effective manner. The study, however, identifies three challenges that remain for CDD projects to be wholly successful. The first challenge is a call for harmonization of CDD mechanisms within the country. CDD approaches are not currently coordinated geographically, technically, or financially. This leaves communities who need help without resources, an excess of skills in some areas and a dearth of skills in others, and funding allocated towards operations, which could be redirected to communities. The report recommends coordinating and consolidating CDD approaches. The second challenge is the achievement of inclusive participation. While empowerment has proven to improve the well-being of communities, not all local officials recognize the benefits of a participatory approach. The report recommends operating in districts on a long-term basis to develop sustained empowerment and extensive training to local officials and communities on participatory approaches. The final challenge for CDD projects is the funding of livelihood activities, which is necessary for sustained poverty reduction. Evidence has demonstrated that CDD backing of livelihood activities through loans, however, is unsuccessful. The report recommends administering grants for livelihood activities and ensuring technical support along with a participatory approach.